2022
DOI: 10.3390/ijerph192013646
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Contamination of Ambulance Surfaces and Effectiveness of Routine Decontamination Procedure: A Classic Hygiene Lesson for A Novel Pathogen

Abstract: The efficacy of standard operating procedures (SOPs) for the decontamination of ambulances against SARS-CoV-2 has been debated. In Italy, the differential use of ambulances was implemented by regional health authorities, with selected vehicles being used exclusively for transporting COVID-19 patients. We investigated the presence of SARS-CoV-2 on high-touch surfaces in ambulances to assess contamination dynamics and the effectiveness of decontamination SOPs. Four high-touch surfaces were sampled before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Notably, our survey confirmed that manual hand cleaning was the most commonly used decontamination method. While it is less expensive, it takes more time and poses contamination risks to emergency personnel [25,26]. "No-contact" techniques such as chlorine dioxide or hydrogen peroxide vaporization and UV-light decontamination [27] have been available for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our survey confirmed that manual hand cleaning was the most commonly used decontamination method. While it is less expensive, it takes more time and poses contamination risks to emergency personnel [25,26]. "No-contact" techniques such as chlorine dioxide or hydrogen peroxide vaporization and UV-light decontamination [27] have been available for many years.…”
Section: Discussionmentioning
confidence: 99%
“…Nebulized agents seem to have greater efficacy, due to their capability of penetrating areas difficult to reach with a regular cleaning procedure, providing a sealed closure of ambulance cabins. 11 Notably, adequate ventilation time is required after the use of chemical products. Depending on the employed method, the decontamination process requires approximately 20 to 30 minutes to complete (including 10-15 minutes of aeration, when required).…”
Section: A Lean Thinking Analysis Of Ambulance Decontamination Method...mentioning
confidence: 99%
“…Post-bathing, the bodies undergo another round of disinfection, utilizing a 5% sodium hypochlorite solution. After this process, the bodies are again wrapped and placed inside nylon sheets before burial [6,7].…”
mentioning
confidence: 99%